Fostering Work Readiness in Gen Z through Quintuple Helix, 4P's Creativity - Daud, Ilzar; Rahmayani, Melia Wida; Nugraha, Syahrul; Suryathi, Wayan; Hidayat, Danny (Universitas Brawijaya, Indonesia, 2024)
This study aims to explore gender differences in creativity exploration and work readiness among Generation Z employees in the workplace. It integrates the Quintuple Helix model with the 4P's creativity model to comprehensively understand how gender dynamics influence individuals' creative potential and readiness to thrive professionally. The study employed a quantitative approach, distributing questionnaires to 501 students with entrepreneurial experience. Path analysis with Partial Least Square (PLS) was used to analyze the data, including factors like factor loading, construct reliability, Average Variance Extracted (AVE), and discriminant validity. Structural equation modelling assessed direct, indirect, and overall effects. The results indicate that integrating the Quintuple Helix and 4P's creativity models positively impacts creativity exploration and work readiness. Gender dynamics influence individuals' self-perceptions, participation in creative processes, creative outcomes, and access to opportunities. Addressing gender biases and promoting inclusivity in skill development, collaborative processes, product design, leadership, and supportive policies can enhance work readiness for individuals of all genders. The study suggests that organizations and policymakers should proactively challenge gender stereotypes and biases, foster an inclusive culture, provide equal skill development opportunities, promote collaboration, challenge product biases, encourage gender diversity in leadership, and implement supportive policies. These actions can create a more equitable and innovative work environment that harnesses the full creative potential of the workforce and enhances overall work readiness.